Metal-resin composite molded product, manufacturing method for metal-resin composite molded product, and processing method for metal member
By forming a spherical metal cluster on the metal surface and joining it with a polyarylene sulfide resin, the method addresses airtightness and durability issues in metal resin composites, ensuring stability under thermal stress.
Patent Information
- Application Number
- JP2023118481
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-07-20
AI Technical Summary
Existing methods for joining metal and resin materials face challenges in ensuring airtightness and durability under temperature changes, particularly in applications where thermal expansion coefficients differ significantly, leading to potential gaps and damage.
A metal resin composite product is formed by irradiating the metal surface with a high-energy beam to create a substantially spherical metal cluster with an average vertex curvature of 3000 to 6000 (1/mm), which is then joined with a polyarylene sulfide-based resin composition to enhance adhesion and maintain airtightness.
The method ensures airtightness is maintained even after heat shock tests, preventing gaps and damage due to thermal expansion, thereby expanding the applications of metal resin composites.
Smart Images

Figure 2025015217000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a technique for bonding a metal member to a polyarylene sulfide resin composition. [Background technology]
[0002] By combining materials with different properties, such as electrically conductive materials such as metals and electrically insulating materials such as resins, parts that are lighter in weight, stronger, or more functional are being used in various fields. For example, metal-resin composite molded products in which metal members are bonded to thermoplastic resins are used in automobile interior parts such as console boxes around instrument panels, engine-related parts, interior parts, housings, interface connections, and power terminals of electronic devices such as digital cameras and mobile phones. Generally, bonding and screwing are known as methods for joining different materials such as metal and resin, but these are not desirable because they increase the number of steps and parts required. Therefore, various methods for joining metal and resin materials have been proposed.
[0003] For example, Patent Document 1 describes a method of laser processing the surface of a metal material in a certain scanning direction, and then laser processing in another scanning direction crossing the aforementioned scanning direction, and joining a different material to the surface. Patent Document 2 describes a method of improving the joining strength when joining a resin molded product to the surface by setting the undercut rate of the unevenness to a predetermined range when forming unevenness on the surface of a metal plate. Patent Document 3 describes a composite molded body of metal and resin in which a crater-like depression is formed in the metal by a laser beam or the like, and granular sputtering is formed on the ridge-like protuberance where the metal surface is melted and scattered. Patent Document 4 describes a composite structure formed by joining a surface-roughened metal member and a polyarylene sulfide resin composition member, in which the number average developed area ratio (Sdr) of the interface is in the range of 5 or more when any five points on the surface of the surface-roughened metal member are measured in accordance with ISO (International Organization for Standardization) 25178 using a confocal microscope, and the melt viscosity of the PPS resin is in the range of 15 to 500 [Pa·s]. Furthermore, Patent Document 5 discloses a metal insert part and a method for manufacturing a resin molded product using a metal insert part, with the aim of producing an insert mold made of a resin material and a metal material that ensures airtightness and excellent durability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4020957 [Patent Document 2] JP 2020-116806 A [Patent Document 3] JP 2013-71312 A [Patent Document 4] Patent No. 6819798 [Patent Document 5] Patent No. 6615478 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the conventional method of joining metal materials and resin materials, it is not possible to ensure sufficient airtightness at the joint between the metal material and the resin material (i.e., problems such as gaps may occur at the joint between the metal material and the resin material), and there is a demand for improving this point. In addition, when a metal-resin composite molded product is used in an environment where the temperature changes are large, such as in the peripheral parts of an automobile engine, problems may arise because the expansion and contraction rates (so-called linear expansion coefficients) due to temperature changes are extremely different between resin and metal. For example, when the resin member of the metal-resin composite molded product is thin or has a portion with a large change in thickness, or when the metal member has a sharp corner, there is a problem that the metal-resin composite molded product is broken by temperature changes during use. For this reason, the current situation is that the uses and shapes of metal-resin composite molded products are quite limited. Therefore, there is a strong demand for metal-resin composite molded products that can withstand temperature changes over a long period of time. Therefore, the present invention aims to provide a method for producing a metal-resin composite molded product in which a metal member and a polyarylene sulfide-based resin composition member are bonded together, in which the bonded portion does not lose airtightness even after a heat shock test, a method for producing the metal-resin composite molded product, and a method for processing a metal member. [Means for solving the problem]
[0006] A first aspect of the present invention is a metal-resin composite molded article in which a metal member and a polyarylene sulfide-based resin composition member are bonded together. This metal-resin composite molded article uses a polyarylene sulfide-based resin composition, and substantially spherical metal clusters are formed on a surface portion of one side of the metal member that is bonded to the polyarylene sulfide-based resin composition member, and the arithmetic mean curvature of the apex of the metal cluster is 3000 to 6000 (1 / mm).
[0007] A second aspect of the present invention is a method for processing a metal member for a metal-resin composite molded product in which the metal member and a polyarylene sulfide-based resin composition member are bonded together. In this processing method, a high-energy beam is irradiated onto the surface of the metal member to form substantially spherical metal clusters on the metal surface, the metal clusters having arithmetic mean curvatures of apexes of 3000 to 6000 (1 / mm).
[0008] A third aspect of the present invention is a method for producing a metal-resin composite molded product in which a metal member and a polyarylene sulfide-based resin composition member are bonded together. In this method, a surface of the metal member is irradiated with a high-energy beam to form substantially spherical metal clusters on the surface of the metal member, the metal clusters having an arithmetic mean curvature of apexes of 3000 to 6000 (1 / mm), the metal member on whose surface the substantially spherical metal clusters have been formed is inserted into a mold, and a polyarylene sulfide-based resin composition is injection molded to bond the polyarylene sulfide-based resin composition member to the surface of the metal member. Effect of the Invention
[0009] According to an embodiment of the present invention, the joint portion of a metal resin composite molded product in which a metal member and a member made of a polyarylene sulfide resin composition are joined together does not lose airtightness even after a heat shock test. [Brief description of the drawings]
[0010] [Figure 1] 1A to 1C are diagrams illustrating a method for processing a metal member according to an embodiment of the present invention. [Diagram 2] 1A and 1B are diagrams showing exemplary metal clusters formed in laser-irradiated portions of a metal member. [Diagram 3] FIG. 2 is a diagram illustrating the state of the interface between a metal member and a polyarylene sulfide-based resin composition member in accordance with the size of the Spc on the surface of the polyarylene sulfide-based resin composition member in a metal-resin composite molded product according to one embodiment. [Figure 4] FIG. 2 is a diagram showing the shape of a test piece used in an airtightness test. [Diagram 5] FIG. 1 is a diagram showing a schematic configuration of a test device for an airtightness test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, a metal-resin composite molded product according to one embodiment of the present invention will be described. In one embodiment, a metal resin composite molded product is a product in which a metal member and a resin composition member, particularly a polyarylene sulfide-based resin composition member, are joined together. In this metal resin composite molded product, a substantially spherical metal cluster is formed on one surface of the metal member that is joined to the polyarylene sulfide-based resin composition member. The term "substantially spherical" does not limit the shape of each of the metal clusters to a perfect sphere, but also includes shapes of spheroids and shapes in which a part of a sphere or spheroid is missing. The substantially spherical metal clusters can be formed by, for example, irradiating the surface of the metal member with a laser. As a result of intensive research, the inventors of the present application have found that it is possible to form spherical metal clusters on the metal surface by irradiating the surface of the metal member with a laser under predetermined irradiation conditions, thereby improving the airtightness of the joint surface between the metal member and the resin composition member of a metal-resin composite molded product after a heat shock test compared to the conventional method. The shapes of the metal member, the resin composition member, and the metal-resin composite molded product are not particularly limited.
[0012] The metals constituting the metal members contained in the metal-resin composite molded product are not limited to, but include, for example, aluminum, copper, silver, gold, iron, titanium, nickel, magnesium, zinc, and alloys thereof such as carbon steel and stainless steel. The surface of the metal member may be subjected to a surface treatment such as anodizing or painting. From the viewpoint of light weight and strength, it is preferable to use aluminum, magnesium, copper, or titanium as the metal, and in applications requiring electrical conductivity such as terminals, it is more preferable to use aluminum or copper, and copper is particularly preferred. In applications requiring thin-walled rigidity, it is particularly preferable to use magnesium or titanium, and in particular titanium.
[0013] [Polyarylene sulfide resin] The polyarylene sulfide resin (hereinafter sometimes referred to as "PAS resin") used in the polyarylene sulfide resin composition is characterized by excellent mechanical properties, electrical properties, heat resistance and other physical and chemical properties, as well as good processability. Polyarylene sulfide resin is a polymer compound mainly composed of -(Ar-S)- (Ar represents an arylene group, and Ar-S represents an arylene sulfide group) as a repeating unit, and in this embodiment, a polyarylene sulfide resin having a generally known molecular structure can be used.
[0014] Examples of the arylene group include p-phenylene group, m-phenylene group, o-phenylene group, substituted phenylene group, p,p'-diphenylenesulfone group, p,p'-biphenylene group, p,p'-diphenyleneether group, p,p'-diphenylenecarbonyl group, naphthalene group, etc. The PAS resin may be a homopolymer consisting of only the above repeating units, or a copolymer containing the following different repeating units may be preferable in terms of processability, etc.
[0015] As the homopolymer, a polyphenylene sulfide resin using a p-phenylene group as an arylene group and having a p-phenylene sulfide group as a repeating unit is preferably used. As the copolymer, a copolymer composed of a combination of two or more different arylene sulfide groups containing the above-mentioned arylene group can be used. Among them, a copolymer composed of a combination of a p-phenylene sulfide group and an m-phenylene sulfide group is particularly preferably used. Among these copolymers, one containing 70 mol % or more, preferably 80 mol % or more of p-phenylene sulfide groups is suitable from the viewpoint of physical properties such as heat resistance, moldability, and mechanical properties. Among these polyarylene sulfide resins, a high molecular weight polymer (e.g., poly p-phenylene sulfide) having a substantially linear structure obtained by condensation polymerization from a monomer mainly composed of a bifunctional halogenated aromatic compound can be particularly preferably used. The polyarylene sulfide resin used in this embodiment may be a mixture of two or more polyarylene sulfide resins having different molecular weights.
[0016] In addition to the linear polyarylene sulfide resin, a polymer can be used in which a small amount of a monomer such as a polyhaloaromatic compound having three or more halogen substituents is used during condensation polymerization to form a partially branched or crosslinked structure. Also used is a polymer in which a low molecular weight linear polymer is heated at high temperature in the presence of oxygen or the like to increase the melt viscosity through oxidative crosslinking or thermal crosslinking, thereby improving moldability. In the present embodiment, the polyarylene sulfide resin composition refers to a composition containing one or more of the polyarylene sulfide resins described above and other additives that are added as necessary.
[0017] [Olefin copolymer] In this embodiment, the olefin copolymer may be added to the polyarylene sulfide resin composition in order to improve the bonding between the metal member and the polyarylene sulfide resin composition member. The olefin copolymer contains an α-olefin, an α,β-unsaturated acid glycidyl ester, and a (meth)acrylic acid ester as copolymerization components. First, the essential copolymerization components will be described.
[0018] In the present invention, the α-olefin is not particularly limited, and conventionally known α-olefins can be used. For example, ethylene, propylene, butylene, etc. are usable α-olefins. Among these α-olefins, ethylene is particularly preferred. Two or more of these α-olefins can be used in combination.
[0019] The glycidyl ester of an α,β-unsaturated acid is a component represented by the following general formula (1). [ka] (R1 in formula (1) represents hydrogen or a lower alkyl group.)
[0020] Examples of the compound represented by the above general formula (1) include glycidyl acrylate, glycidyl methacrylate, glycidyl ethacrylate, etc. In the present invention, it is preferable to use glycidyl methacrylate.
[0021] By including a glycidyl ester of an α,β-unsaturated acid as a copolymerization component, the effect of improving the bonding with metals can be obtained. However, when the content of the copolymerization component derived from the above glycidyl ester increases, the problem of mold deposits becomes more prominent. Conventionally, it has been believed that the cause of mold deposits is the thermal degradation of thermoplastic elastomers such as olefin copolymers at high temperatures. However, in the case of an olefin copolymer containing an α-olefin and a glycidyl ester of an α,β-unsaturated acid as copolymerization components, the problem of mold deposits can be suppressed even when an olefin copolymer is used by reducing the amount of the glycidyl ester of an α,β-unsaturated acid used.
[0022] The acrylic acid ester usable in the embodiment is not particularly limited, and conventionally known acrylic acid esters can be used. Examples of acrylic acid esters that can be used include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, n-hexyl acrylate, n-octyl acrylate, etc.), methacrylic acid and methacrylic acid esters (e.g., methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, n-octyl methacrylate, etc.). Among these acrylic acid esters, the use of methyl acrylate is particularly preferred.
[0023] The olefin copolymer used in the embodiment may contain other copolymer components as long as the effects of the present invention are not impaired.
[0024] The olefin copolymer used in the embodiment can be produced by polymerization using a conventionally known method.
[0025] The content of the olefin copolymer contained in the composition of the present invention is not particularly limited. In an embodiment, the olefin copolymer is preferably contained in an amount of 0 to 20 parts by mass, more preferably 1% by mass or more and 15% by mass or less, relative to 100 parts by mass of the polyarylene sulfide resin.
[0026] [Inorganic filler] In the resin composition of the present invention, an inorganic filler can be blended for the purpose of improving performance such as mechanical strength, heat resistance, dimensional stability (resistance to deformation, warpage), and electrical properties. As the inorganic filler, a fibrous, powdery, or plate-like filler is used according to the purpose. Examples of the fibrous filler include inorganic fibrous materials such as glass fiber, asbestos fiber, carbon fiber, silica fiber, silica-alumina fiber, zirconia fiber, boron nitride fiber, boron fiber, potassium titanate fiber, and further fibrous materials of metals such as stainless steel, aluminum, titanium, copper, and brass. Particularly representative fibrous fillers are glass fiber and carbon fiber. On the other hand, examples of the powdered filler include carbon black, silica, quartz powder, glass beads, glass powder, calcium silicate, aluminum silicate, kaolin, talc, clay, diatomaceous earth, silicates such as wollastonite, metal oxides such as iron oxide, titanium oxide, zinc oxide, and alumina, metal carbonates such as calcium carbonate and magnesium carbonate, metal sulfates such as calcium sulfate and barium sulfate, silicon carbide, silicon nitride, boron nitride, and various metal powders. Examples of the plate-like filler include mica, glass flakes, and various metal foils. In an embodiment, it is preferable to use glass fiber, calcium carbonate, and glass beads, or a combination of these. It is to be noted that these inorganic fillers can be used alone or in combination of two or more.
[0027] In the embodiment, the content of the inorganic filler is preferably 0 to 80 parts by mass, more preferably 0 to 75 parts by mass, relative to 100 parts by mass of the polyarylene sulfide resin. If the content of the inorganic filler is more than 75 parts by mass, the melt viscosity of the polyarylene sulfide-based resin composition increases, so that the polyarylene sulfide-based resin is not filled in the metal cluster portion on the surface of the metal member, and airtightness between the metal member and the polyarylene sulfide-based resin composition member may not be obtained.
[0028] [Other ingredients] The polyarylene sulfide-based resin composition used in the embodiment may contain other resins as long as the effects of the present invention are not impaired. In addition, the polyarylene sulfide-based resin composition used in the present invention also includes compositions to which desired properties have been imparted by adding a nucleating agent, a pigment such as carbon black or an inorganic calcined pigment, an antioxidant, a stabilizer, a plasticizer, a lubricant, or a release agent in order to impart desired properties to a molded product.
[0029] [Polyarylene sulfide resin composition] The polyarylene sulfide resin composition of the embodiment can be prepared by a conventionally known method. For example, the method of preparing pellets by mixing each component and then kneading and extruding the mixture with an extruder, the method of preparing pellets with different compositions, mixing a predetermined amount of the pellets and subjecting them to molding, and obtaining a molded product with a target composition after molding, and the method of directly charging one or more of each component into a molding machine can be used.
[0030] The method of joining the metal member and the polyarylene sulfide-based resin composition member is described in detail below, but is not particularly limited. For example, they can be joined by a welding method such as ultrasonic welding, vibration welding, laser welding, etc., or injection molding. For example, it is preferable to join them by insert molding using a metal material as an insert member. The metal member used in the embodiment and the processing method thereof will be described later. In one embodiment, it is preferable that the surface part of one surface of the metal member that is joined to the polyarylene sulfide-based resin composition member has substantially spherical metal clusters as described above. The arithmetic mean curvature of the apex of the metal cluster is preferably 3000 to 6000 (1 / mm). The arithmetic mean curvature of the apex of the metal cluster will be described in detail below. In addition, the metal resin composite molded product of one embodiment is characterized in that the airtightness of the joint between the metal member and the polyarylene sulfide resin composition member is almost the same before and after 1000 cycles of a heat shock test, in which one cycle is left at a temperature of -40°C for 30 minutes and left at a temperature of 150°C for 30 minutes. The heat shock test, also called a thermal shock test, is a test in which a substance is repeatedly subjected to rapid temperature changes to expand and contract the substance, thereby generating thermal stress and thermal distortion inside the substance, and observing whether defects such as cracks occur in the substance. In the Japanese Industrial Standards (JIS), the standard for the test method is specified in JIS C 60068-2-14(Na) (Environmental Test Method-Electrical and Electronic). In one embodiment, the metal-resin composite molded product is repeatedly subjected to a heat shock test (for example, 1000 cycles) in which one cycle is left at a temperature of -40 ° C for 30 minutes and left at a temperature of 150 ° C for 30 minutes, and the airtightness of the joint between the metal member and the polyarylene sulfide-based resin composition member is observed to see whether or not there is a defect in the airtightness. Here, the airtightness of the joint between the metal member and the polyarylene sulfide-based resin composition member simply refers to the presence or absence of a gap at the joint between the metal member and the polyarylene sulfide-based resin composition member, and if it is observed that a gap that did not exist before the heat shock test has occurred after the heat shock test, it is evaluated that the airtightness has decreased. The airtightness of the joint between the metal member and the polyarylene sulfide-based resin composition member being almost the same before and after the heat shock test means that the airtightness does not change at all, and that the degree of increase or decrease in airtightness is slight. Here, the airtightness of the joint between the metal member and the polyarylene sulfide-based resin composition member is measured by using a dedicated measuring device such as an airtightness measuring device to flow a specific gas at a specific detection pressure and detect the gas leaking from the joint. The airtightness of the joint between the metal member and the polyarylene sulfide-based resin composition member can be measured, for example, by a helium leak test vacuum method or the like.
[0031] The second embodiment of the present invention is a method for processing a metal member for producing a metal-resin composite molded product in which the metal member and the polyarylene sulfide-based resin composition member are joined together. Fig. 1 shows a schematic diagram of the method for processing a metal member according to the second embodiment. As shown in Figure 1, when a metal component is irradiated with a laser, the metal on the surface of the metal component is melted by the high-energy beam of the laser, pushed out to the outside of the irradiated area, and then solidified into a spherical shape due to surface tension. The metal component surface is scanned with the laser at a fine pitch, generating spherical objects that overlap to form metal clusters. Alternatively, when the metal component sublimes, the scattered liquid metal particles solidify (re-adhere) and accumulate, forming spherical metal clusters. Figure 2 shows an image of an exemplary metal cluster formed in the laser irradiated area when a metal component is irradiated with a laser. Here, if the laser output (energy per unit time) is low, the metal on the metal surface may not melt, or sublimation or scattering of liquid metal particles may not occur. Therefore, the laser output for forming spherical metal clusters is appropriately determined according to the metal material used for the metal member. In addition, in order to make the molten metal pushed out to the outside of the laser irradiation area into a minute sphere, the laser scanning pitch is preferably 30 μm or less, more preferably 20 μm or less, or even more preferably 10 μm or less. The energy given to the metal surface per unit area per unit time is determined by the laser output and the irradiation speed. Therefore, in addition to the laser output, the irradiation speed is also a factor in forming spherical metal clusters. With the appropriate laser output and irradiation speed, a local temperature rise occurs on the metal surface in a very short time, thereby forming spherical metal clusters. By using the processing method for metal members of the second embodiment, a substantially spherical metal cluster can be formed on the surface portion of one surface of the metal member used in the metal-resin composite molded product of the first embodiment that is joined to the polyarylene sulfide-based resin composition member.
[0032] From the viewpoint of ensuring sufficient airtightness of the joint surface between the metal member and the polyarylene sulfide-based resin composition member, it is preferable that spherical metal clusters are formed on the entire surface of the joint surface between the metal member and the polyarylene sulfide-based resin composition member. To achieve this, it is preferable to set the scanning pitch of the laser smaller than the irradiation diameter of the laser.
[0033] In this disclosure, the term "high energy beam" means a beam with energy per unit time high enough to form spherical metal clusters on the surface of a metal member. The high energy beam is typically, but not necessarily, a laser, and may be a beam generated by an electron gun. In the second embodiment, it is preferable to irradiate the surface of the metal member with a high-energy beam to form substantially spherical metal clusters on the surface of the metal member, the metal clusters having an arithmetic mean curvature of the apex of the metal cluster being 3000 to 6000 (1 / mm). The arithmetic mean curvature of the apex of the metal cluster will be described in detail later.
[0034] The third embodiment is a method for producing a metal-resin composite molded product in which a metal member and a polyarylene sulfide-based resin composition member are joined. The method for producing a metal-resin composite molded product of the third embodiment is a method for forming substantially spherical metal clusters on the surface of the metal member by irradiating the surface of the metal member with a high-energy beam such as a laser, and melt-joining the metal member on which the substantially spherical metal clusters are formed on the metal surface and the polyarylene sulfide-based resin composition member. By forming spherical metal clusters on the joint surface between the metal member and the polyarylene sulfide-based resin composition member, when the metal member and the polyarylene sulfide-based resin composition member are insert molded, the molten polyarylene sulfide-based resin composition enters the spherical metal clusters, and the adhesion between the metal and the polyarylene sulfide-based resin composition is increased in the molding stage. Therefore, in the produced metal-resin composite molded product, the joint surface between the metal member and the polyarylene sulfide-based resin composition member has higher airtightness than conventional ones.
[0035] The area where the spherical metal clusters are formed on the surface of the metal member is preferably the entire surface of the joint surface between the metal member and the polyarylene sulfide-based resin composition member, but is not limited thereto. For example, if the spherical metal clusters are formed on most of the joint surface, for example, 70 to 80% or more of the joint surface, a sufficiently high airtightness is ensured on the joint surface between the metal member and the polyarylene sulfide-based resin composition member. For example, when the entire joint surface between the metal member and the polyarylene sulfide-based resin composition member is irradiated with a laser, if the scanning pitch of the laser is larger than the irradiation diameter of the laser, there will be an area on the joint surface that is not irradiated with the laser. Even in this case, if the area on the joint surface that is not irradiated with the laser is relatively small, a sufficiently high airtightness is ensured on the joint surface between the metal member and the polyarylene sulfide-based resin composition member.
[0036] The present inventors further focused on the shape of the spherical metal clusters formed on the surface of the metal member, and conducted research into the relationship between various surface roughness parameters of the surface of the metal member and the airtightness of the joint surface between the metal member and the polyarylene sulfide-based resin composition member. As a result, it was found that the airtightness of the joint surface between the metal member and the polyarylene sulfide-based resin composition member can be maintained good even after a heat shock test by setting the Spc (arithmetic mean curvature of the peak) of the apex of the spherical metal cluster within a predetermined range. Spc (arithmetic mean curvature of the peak) is a parameter of the surface quality defined in ISO 25178, and represents the average value of the principal curvature of the peaks formed on the surface to be evaluated. A small Spc indicates that the point (peak) that comes into contact with another object (in the embodiment, the polyarylene sulfide-based resin composition member) is rounded, and a large Spc indicates that the point that comes into contact with another object is sharp.
[0037] The reason why the airtightness of the joint surface of the metal member with the resin is almost the same before and after the heat shock test when the Spc of the apex of the spherical metal cluster is within a certain range can be inferred as follows, referring to Figure 3. FIG. 3 is a schematic diagram showing the joint surface between a metal member and a polyarylene sulfide-based resin composition member when the Spc of the apex of the spherical metal cluster formed on the surface of the metal member is large ("Spc large"), medium ("Spc medium"), and small ("Spc small"). When the Spc on the metal member surface is large, the apex of the spherical metal cluster has a sharp shape. When the polyarylene sulfide-based resin composition in contact with this surface is cooled, sink marks (shrinkage) occur, but if the apex of the metal cluster is sharp, a gap is likely to occur between the polyarylene sulfide-based resin composition and the metal at the joint surface of the apex, which is disadvantageous in terms of achieving high airtightness. On the other hand, when the Spc on the metal member surface is small, the spherical metal cluster has a surface property that changes gradually as a whole. The surface area of the joint between the metal member and the polyarylene sulfide-based resin composition member is small, and the adhesion between the metal member and the polyarylene sulfide-based resin composition member is not easily increased during the molding stage of the metal-resin composite molded product. Therefore, when the Spc on the metal member surface is medium, the molten polyarylene sulfide-based resin composition penetrates sufficiently into the spherical metal clusters on the surface of the metal member, and the fine clusters on the metal member surface can form many anchors with the resin. Therefore, it is unlikely that loosening (leak paths) of the joint caused by the expansion and contraction of the resin during the heat shock test will be formed, and it is presumed that the adhesion between the metal member and the polyarylene sulfide-based resin composition member of the metal-resin composite molded product can be kept extremely high even after the heat shock test.
[0038] Specifically, the Spc of the apexes of the spherical metal clusters on the surface of the metal member is preferably in the range of 3000 to 6000 (1 / mm), and more preferably in the range of 4500 to 4700 (1 / mm). In order to adjust this Spc to be within a desired range, the energy given by laser irradiation to the surface that will be the joint surface between the metal member and the polyarylene sulfide-based resin composition member is controlled. When a pulsed laser is used as the laser, the energy E per pulse is expressed as P / f, where P is the average output and f is the frequency. Therefore, by adjusting the average output P (so-called laser output) and / or the frequency f, the energy given to the surface that will be the joint surface between the metal member and the polyarylene sulfide-based resin composition member can be controlled. For example, when the frequency of the pulsed laser is increased, the amount of energy per pulse given to the surface of the metal member becomes smaller, so that Spc tends to decrease. Conversely, when the frequency of the pulsed laser is decreased, the amount of energy per pulse given to the surface of the metal member becomes larger, so that Spc tends to increase, but when the amount of energy becomes sufficiently large, Spc becomes saturated.
[0039] The particle size of the particles constituting the metal cluster is preferably 1 to 500 μm, more preferably 5 to 300 μm, and particularly preferably 10 to 200 μm. If the particle size is less than 1 μm, the polyarylene sulfide resin may not fill the gaps between the particles constituting the resin cluster, and adhesion may not be obtained. If the particle size exceeds 500 μm, a gap may occur between the metal member and the resin due to shrinkage of the polyarylene sulfide resin after molding, and airtightness may not be obtained.
[0040] The method of joining the metal member and the polyarylene sulfide-based resin composition member is not limited, but can be joined by a welding method represented by ultrasonic welding, vibration welding, laser welding, etc., or injection molding. For example, they can be joined by insert molding using a metal material as an insert member. That is, a metal member having spherical metal clusters formed on its surface as described above is inserted into a mold, a polyarylene sulfide-based resin composition is injected into the mold, and these are molded together to join the polyarylene sulfide-based resin composition member to the surface of the metal member. EXAMPLES
[0041] [Manufacturing of metal-resin composite moldings] The production of the metal-resin composite molded product will be specifically described below. In the examples, a metal resin composite molded article 10 (hereinafter referred to as "test piece 10") having a shape shown in FIG. 4 was prepared as a test piece. As shown in Fig. 4, the test piece 10 consisted of a circular metal member 11 having an inner hole in the center, and a resin molded product 12 placed in the inner hole of the metal member 11. The metal member 11 had an outer diameter of φ50 mm, an inner hole diameter of φ20 mm, and a thickness of 1 mm. The resin molded product 12 had an outer diameter of φ30 mm and a thickness of 3 mm.
[0042] The components used in the materials constituting the metal member 11 and the resin molded product 12 are as follows: Metal parts: Aluminum A5052 Polyarylene sulfide resin composition: Polyarylene sulfide resin 1: Fortron KPS manufactured by Kureha Corporation (melt viscosity: 20 Pa·s (shear rate: 1200 sec -1 , 310℃) Polyarylene sulfide resin 2: Fortron KPS manufactured by Kureha Corporation (melt viscosity: 28 Pa·s (shear rate: 1200 sec -1 , 310℃) Polybutylene terephthalate resin: "300FP" manufactured by Polyplastics Co., Ltd. Polyethylene terephthalate resin: "PET II" manufactured by Takayasu Co., Ltd. Olefin copolymer 1: "Bondfast 7L" manufactured by Sumitomo Chemical Co., Ltd. Olefin copolymer 2: "Bondfast 7M" manufactured by Sumitomo Chemical Co., Ltd. Glass fiber 1: "CS GL-HF" manufactured by Owens Corning Manufacturing Co., Ltd. Glass fiber 2: "ECS03T747" manufactured by Nippon Electric Glass Co., Ltd. Glass fiber 3: "ECS03T747H" manufactured by Nippon Electric Glass Co., Ltd. Glass fiber 4: "ECS03T187" manufactured by Nippon Electric Glass Co., Ltd. Calcium carbonate: Asahi Komatsu Co., Ltd. "MC-35W" Carbon black: "MA600B" manufactured by Mitsubishi Chemical Corporation Pentaerythritol stearate: Emery Oleochemicals Japan LOXYOL VPG861 Antioxidant: "Irganox 1010" manufactured by BASF Japan Ltd. Phosphorus stabilizer: Monobasic calcium phosphate manufactured by Taihei Chemical Industry Co., Ltd. The component ratios of the polyarylene sulfide resin composition, which is the material of the resin molded product, are shown in Table 1. The melt viscosity of the polyarylene sulfide resin composition shown in Table 1 was measured in accordance with ISO 11433 as follows. A Capillograph manufactured by Toyo Seiki Seisakusho Co., Ltd. was used, and a flat die of 1 mm diameter x 20 mm length was used as the capillary. The barrel temperature was 310°C, and the shear rate was 1000 sec. -1 The melt viscosity was measured under the following conditions.
[0043] [Table 1]
[0044] Before bonding to the resin molded product 12, a laser processing was performed concentrically on the surface of the metal member 11 within a range of φ20 mm to φ26 mm (the bonding surface with the resin molded product 12) using a laser processing machine (ML-7350DL manufactured by Amada Weld Tech). Table 2 below shows the laser irradiation conditions for Examples 1 and 2 and Comparative Examples 1 and 2. Although not shown in the table, the laser irradiation pitch was 10 μm and the irradiation diameter was 58 μm for all Examples and Comparative Examples. The pitch is the distance between the concentric circles scanned by the laser. Since the pitch is smaller than the irradiation diameter, the entire joint surface between the metal member 11 and the resin molded product 12 is irradiated with the laser.
[0045] In all the examples and comparative examples, the surface of the metal member 11 was observed with a scanning electron microscope (SEM), and it was confirmed that spherical metal clusters were formed over the entire surface. Furthermore, the Spc of the apex of the spherical metal cluster formed on the surface of the metal member 11 was measured using a Keyence VK-X3000 laser microscope (see Table 2).
[0046] After performing laser processing on the metal member 11, insert molding was performed using the metal member 11 as an insert member and each material listed in Table 1 as a resin composition under the following conditions, and the metal member 11 and the resin molded product 12 were joined to form a test piece 10 of a metal-resin composite molded product shown in Figure 4. The insert molding conditions were as follows: Injection molding machine: Sodick TR100EH Cylinder temperature: 320°C (Examples 1 to 3) 260°C (Comparative Examples 1 and 2) Mold temperature: 150°C (Examples 1 to 3) 150°C (Comparative Examples 1 and 2) ·Injection speed: 15mm / s - Holding pressure: 50MPa
[0047] [Airtightness test] Next, for the test pieces 10 molded as the examples and comparative examples, an airtightness test was performed on the joint surface between the metal member 11 and the resin molded article 12. The configuration of the test device for the airtightness test (helium leak test, vacuum method) is shown in FIG. As shown in FIG. 5, the jig 2 and the test piece 10 were placed in the chamber 3, which was sealed from the outside. The jig 2 was in the shape of a rectangular parallelepiped with a bottom, and by placing the test piece 10 on the top, the inside of the jig 2 was sealed from the rest of the inside of the chamber 3. With the valve 6 in the open state, the inside of the jig 2 was evacuated by the vacuum pump 5, and then with the valve 6 in the closed state, the chamber 3 was filled with helium gas by the helium cylinder 4. Helium gas leaking from the joint of the test piece 10 in the chamber 3 was detected by the helium detector 7. The control device 8 displayed the detection result of the helium gas. As the helium detector 7, a helium leak tester G-FINE manufactured by Cosmo Instruments Co., Ltd. and an L300i manufactured by Inficon Co., Ltd. were used.
[0048] The helium pressure in the chamber 3 was set to 400 kPa, and the vacuum pressure in the jig 2 was set to 100 kPa. If the joint between the metal member 11 and the resin molded product 12 of the test piece 10 is not airtight, the helium gas in the chamber 3 flows into the jig 2 and is detected by the helium detector 7. In this test, the helium pressure detected by the helium detector 7 (detection pressure) was 1.0×10 -7 (In the table, it is written as "1.0E-7") Pa·m 3 / s or more, it is judged as poor airtightness, and 1.0 x 10 -7 (1.0E-7) Pa·m 3 If the value was less than / s, the airtightness was judged to be good.
[0049] [Heat shock test] A heat shock test was carried out using thermal shock testers ES-106LH and ES-77LHS manufactured by Hitachi Appliances, Inc. For Examples 1 to 3, one cycle consisted of leaving at -40°C for 30 minutes and leaving at 150°C for 30 minutes, and the resin molded product was taken out of the tank for the airtightness test described above every 250 cycles to evaluate the cold and heat shock resistance (heat shock resistance). For Comparative Examples 1 and 2, one cycle consisted of leaving at -40°C for 30 minutes and leaving at 125°C for 30 minutes, and the resin molded product was taken out of the tank for the airtightness test described above every 250 cycles to evaluate the cold and heat shock resistance. Each heat shock test was carried out up to 1000 cycles. Regarding the detection pressure of the air tightness test on the test piece, Table 2 shows the results of Examples 1 to 3 and Comparative Examples 1 and 2.
[0050] [Table 2]
[0051] According to Table 2, it was confirmed that when the Spc of the apex of the metal cluster of the metal member in the composite molded product of the polyarylene sulfide-based resin composition member and the metal member is 4500 to 4700 (1 / mm), the joint between the metal member and the polyarylene sulfide-based resin composition member has high airtightness even after the heat shock test. From Comparative Examples 1 and 2, even if the Spc of the metal member is within the above range, in the composite molded product of the polybutylene terephthalate-based resin composition member and the metal member, the resin molded product cracked and broke, and the joint could not be airtight after the heat shock test.
[0052] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment. Furthermore, the above embodiment can be improved or modified in various ways without departing from the spirit of the present invention. [Explanation of symbols]
[0053] 2…Jig 3. Chamber 4. Helium tank 5…Vacuum pump 6. Valve 7…Helium detector 8...Control device 10…Metal resin composite molded product 11...Metal parts 12…Resin molded product
Claims
1. A metal-resin composite molded product in which a metal member and a polyarylene sulfide-based resin composition member are bonded, a surface portion of one surface of the metal member that is bonded to the polyarylene sulfide-based resin composition member has substantially spherical metal clusters; the arithmetic mean curvature of the apex of the metal cluster is 3000 to 6000 (1 / mm); A metal-resin composite molded product in which the airtightness of a joint between the metal member and the polyarylene sulfide-based resin composition member is approximately the same before and after 1,000 cycles of a heat shock test, one cycle of which is leaving the joint at a temperature of -40°C for 30 minutes and leaving the joint at a temperature of 150°C for 30 minutes.
2. 2. The metal-resin composite molded product according to claim 1, wherein the arithmetic mean curvature of the apex of the metal cluster is 4000 to 5000 (1 / mm).
3. A method for producing a metal-resin composite molded product in which a metal member and a polyarylene sulfide-based resin composition member are joined, comprising the steps of: Irradiating a surface of the metal member with a high-energy beam to form substantially spherical metal clusters on the surface of the metal member, the metal clusters having an arithmetic mean curvature of apexes of 3000 to 6000 (1 / mm); the metal member having the substantially spherical metal clusters formed on the surface of the metal member is inserted into a mold, and a polyarylene sulfide-based resin composition is injection-molded to bond the polyarylene sulfide-based resin composition member to the surface of the metal member; A manufacturing method for metal-resin composite molded products.
4. The method for producing a metal-resin composite molded product according to claim 3, wherein the arithmetic mean curvature of the apex of the metal cluster is 4000 to 5000 (1 / mm).
5. A method for processing a metal member for producing a metal-resin composite molded product in which a metal member and a polyarylene sulfide-based resin composition member are joined, comprising the steps of: A method for processing a metal component, comprising irradiating a surface of the metal component with a high-energy beam to form substantially spherical metal clusters on the surface of the metal component, the metal clusters having an arithmetic mean curvature of apexes of 3000 to 6000 (1 / mm).
6. 6. The method for processing a metal member according to claim 5, wherein the arithmetic mean curvature of the vertices of the metal clusters is 4000 to 5000 (1 / mm).
Citation Information
Patent Citations
Composite molding body of metal member and molded resin member, and surface processing method of metal member
JP2013071312A
Metal component production method, and composite molded body
JP2014117724A
Metal plate, metal plate manufacturing method, metal-resin composite molded article and manufacturing method thereof
JP2020116806A
Component composite and method for manufacturing a component composite
US20110177286A1
METAL MATERIAL HAVING JOINTS WITH DIFFERENT MATERIALS AND METHOD OF PROCESSING THE SAME USING LASER
JP4020957B2